What's wrong with a van? - Brandenberg, Franz (New York : Greenwillow Books, 1987)
Edward and Elizabeth think they want a new family car that is not dented or in need of paint, until the beloved old van is taken away and they find themselves missing it.
Keywords: Vans -- Fiction